Proceedings of the Invitational Conference on Testing Problems (New York, New York, October 28, 1961) - Educational Testing Service, Princeton, NJ.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1961)
Three themes were addressed at the conference: (1) implications of factor analysis for achievement testing; (2) use of achievement tests in awarding course credits; and (3) extended conceptions of evaluation in higher education. The speeches were entitled: Factors of Verbal Achievement, by John B. Carroll; Schools of Thought in Judging Excellence of English Themes, by John W. French; Factor Analysis of Relevance Judgments: an Approach to Content Validity, by Ledyard R Tucker; Credit and the Advanced Placement Program, by Jack N. Arbolino; The Examining Program at Antioch College, by Ruth D. Churchill; Examinations and Instruction by Television, by Clifford G. Erickson; Credit and Waiver Examinations at Michigan State University, by Willard G. Warrington; Measuring the Quality of a College or University, by Dewey B. Stuit; and the Nature and Use of Institutional Research, by James I Doi. The luncheon address, Management of the Learning Environment, was delivered by John E. Ivey, Jr. A memorial speech in honor of Irving D. Lorge was given by Robert L. Thorndike. (MH)
Educational level discussed: High Schools.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement Tests; Advanced Placement Programs; College Credits; College Entrance Examinations; College Instruction; Conference Reports; Educational Quality; Educational Television; Equivalency Tests; Evaluation; Factor Analysis; High Schools; Higher Education; Institutional Research; Measurement Techniques; Test Validity; Testing Problems; Testing Programs; Verbal Ability; Writing (Composition); Writing Evaluation; Antioch College OH -- Content Validity; Collected Works, Proceedings